Media Pembelajaran Kreatif Finger Painting Membuat Tempat Pensil Edukatif Dari Kaleng Bekas Daur Ulang - Diana; Bunga Eka Dhe Ana (Fusion: Jurnal Pengabdian kepada Masyarakat, 2025)
Creativity and environmental awareness are two important aspects that need to be instilled from an early age through a fun and meaningful learning approach. One effective strategy in early childhood learning is the use of art activities, such as finger painting, combined with creative recycling practices. This study aims to describe the implementation of finger painting as a learning medium for creative recycling at Sirajudin Islamic Kindergarten. The research method used was action research (direct practice) with a qualitative descriptive approach. Finger painting was applied in the activity of decorating used items such as cigarette cans to make attractive and functional pencil cases. The results showed that this activity was able to increase children's enthusiasm, creativity, and active participation in the learning process. In addition, children began to understand the concept of reusing waste as a valuable resource and demonstrated a sense of responsibility towards the surrounding environment. This activity also made a positive contribution to the development of fine motor skills, the ability to recognize colors and textures, and the strengthening of religious values such as cleanliness and social awareness. Thus, recycling-based finger painting not only supports children's cognitive and motor aspects but also forms character and sustainable environmental awareness from an early age